ANALISIS WACANA KRITIS LATAR HISTORIS DALAM PIDATO KENEGARAAN PRESIDEN SUSILO BAMBANG YUDHOYONO - Jupriono, * (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2010)
ABSTRACT. The focus of this study is explicit and implicit meanings of historical setting of Presiden SBY state speech discourse during 2004-2010. By perspective of critical discourse analysis van Dijk, it yields foundings as follows. Presiden SBY state speech maximally has made use of historical discourse setting to lead Indonesian public understanding. In building positive self image, Presiden SBY expresses explicitly life dynamic of politic, economy, law, social during the first ten (10) years of reformation era.Presiden SBY leads public perception implicitly that he is high ligitimated Presiden as democratic campaign product. Besides that, SBY also constructs publicunderstandingthat he gives contribution to reveal the development of Indonesian country. SBY is the more smart Presiden who exlpoits state speech as media of imagery politic. Â Keywords: latar historis, politik pencitraan, makna eksplisit, persepsi implisit, analisis wacana kritis